Cross-sectional analysis of sleep-promoting and wake-promoting drug use on health, fatigue-related error, and near-crashes in police officers. Issue 9 (19th September 2018) - Ogeil, Rowan P; Barger, Laura K; Lockley, Steven W; O'Brien, Conor S; Sullivan, Jason P; Qadri, Salim; Lubman, Dan I; Czeisler, Charles A; Rajaratnam, Shantha M W
Abstract : Objectives: To examine sleep-promoting and wake-promoting drug use in police officers and associations between their use and health (excessive sleepiness, stress and burnout), performance (fatigue-related errors) and safety (near-crashes) outcomes, both alone and in combination with night-shift work. Design: Cross-sectional survey. Setting: Police officers from North America completed the survey either online or via paper/pencil at a police station. Participants: 4957 police participated, 3693 online (91.9%, participation rate) and 1264 onsite (cooperation rate 63.1%). Main outcome measures: Sleep-promoting and wake-promoting drug use, excessive sleepiness, near-crash motor vehicle crashes, dozing while driving, fatigue errors, stress and burnout. Results: Over the past month, 20% of police officers reported using sleep-promoting drugs and drugs causing sleepiness, while wake-promoting agents were used by 28% of police (5% used wake-promoting drugs, 23% used high levels of caffeine and 4% smoked to stay awake). Use of sleep-promoting drugs was associated with increased near-crashes (OR=1.61; 95% CI 1.21 to 2.13), fatigue-related errors (OR=1.75; 95% CI 1.32 to 2.79), higher stress (OR=1.41; 95% CI 1.10 to 1.82), and higher burnout (OR=1.83; 95% CI 1.40 to 2.38). Wake-promoting drug use, high caffeine and smoking to stay awake were associated with increased odds of a fatigue-related error, stress and burnout (ORs ranging from 1.68 to 2.56). Caffeine consumption was common, and while smoking was not, of those participants who did smoke, one-in-three did so to remain awake. Night-shift work was associated with independent increases in excessive sleepiness, near-crashes and fatigue-related errors. Interactions between night-shift work and wake-promoting drug use were also found for excessive sleepiness. Conclusions: Police who use sleep-promoting and wake-promoting drugs, especially when working night shifts, are most vulnerable to adverse health, performance and safety outcomes. Future research should examine temporal relationships between shift work, drug use and adverse outcomes, in order to develop optimal alertness management strategies.